(untitled) - Howell, David C. (Belmont, CA, 2008)
This book provides an understanding of the logic behind the statistics: why and how certain methods are used rather than just doing techniques by rote. It contains an abundance of real data and research studies as a base and moves through an analysis of data.
Keywords: Social sciences,Psychometrics,Đo nghiệm tâm lý,Khoa học xã hội; Statistical methods,Phương pháp thống kê